Univerzitetni študij za medicinske sestre - Pahor, Majda (Obzornik zdravstvene nege, 1998)
The article reparts on the results of the research into the course of university level study of health education (HE) for nurses at the University in Ljubljana. The author proposed two research questions: the first one dealt with the experiencing of university levelstudy by the students themselves, andthe second one with changes in professional image and self image. In the introduction, study program of health education representing the starting point of the present research work, its contents, principles, teaching style, structure and expert assessment are presented. The research strategy was took the form of a two-years prospective study of the case of the first generation of (irregular) students, enrolled in the period 1993 to 1995. The gathering ofdata covered two years, and diffrent instruments were used. Quantitative (statistical) and qualitative processing of the data was used. The results revealed that the study of HE is experienced predominatly positively, and pointed out certain weak points, requiring certain modifications. Changes in professional image reveal that elements of a new professionalism in partnership with health system users are coming into existence.
Keywords: education; Education, nursing, diploma programs; izobraževanje; medicinske sestre; Nursing care; Questionnaires; Students, nursing; Trends; univerzitetni študij; zdravstvena vzgoja